Small Things, Big Impact: The Role of Social Media in Promoting Green Consumerism of Ecofurniture Products - Putri, Dinarti Zata Amani Mulia (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2025)
Objective: This study investigates the role of social media as a tool for promoting ecofurniture as a green product on purchase intention, using variables from the theory of planned behaviour; attitude, subjective norms, and perceived behavioural control as mediating variables. Additionally, this study examines the role of trust and price consciousness as mediators in the relationship between social media as a promoting instrument of green products and purchase intention. Design/Methods/Approach: The data were gathered by conducting a survey questionnaire among 320 respondents who knows ecofurniture through social media. The PLS-SEM technique was used to analysing the collected data. Findings: The study indicates that attitude, trust, product knowledge and perceived consumer effectiveness significantly impact purchase intention. It also finds that perceived social media marketing positively affects subjective norms, perceived consumer effectiveness and product knowledge, while price consciousness, subjective norms, and perceived behavioural control do not have a significant effect on purchase intention. Originality/Value: This study enriches new insights on how perceived consumer effectiveness and purchase intention show inconsistent result from the previous studies. This research seeks to explore this relationship specifically within the ecofurniture context to see if these patterns hold true or vary. Practical/Policy implication: The study demonstrates that consumer attitudes and perceptions of social media significantly impact the intention to purchase eco-furniture products. These findings suggest that eco-furniture producers should strategically utilise social media to emphasise positive attributes, such as the benefits, manufacturing process, and environmental impact of eco-furniture, to shape consumer attitudes and increase the likelihood of actual purchases.